Application Of Problem-Based Learning Model To Improve Students' Ability To Develop Business Ethics And True Entrepreneurial Professionalism - Hidayat, Rachmad; Naswan Suharsono; Iva Khoiril Mala; Mohammad Hari; Annisa Rahmawati; Dewi Zahro Pertiwi (International Journal of Technology and Education Research, 2025)
This study aims to determine the effect of the Problem-Based Learning (PBL) model on students' ability to find alternative solutions, both through group work and independently. The method used in this study is a quantitative method with an experimental design. The research sample consisted of 99 students enrolled in the 2022 Business and Professional Ethics course at Malang State University, divided into three classes, N, P, and O. The experimental group used the PBL model, while the control group used the conventional learning model. Data were collected through observation and PBL assignments in accordance with the DNA criteria of Malang State University. The analysis technique used statistical tests with the help of SPSS software. The results showed that there was a significant difference between the experimental and control groups in terms of the ability to find alternative solutions. The PBL model proved to be more effective in improving this ability, both in the context of group work and independent learning